Protein adsorption at the electrified air-water interface: Implications on foam stability - Engelhardt, Kathrin; Rumpel, Armin; Walter, Johannes; Dombrowski, Jannika; Kulozik, Ulrich; Braunschweig, Björn; Peukert, Wolfgang (Langmuir, 2012)
The surface chemistry of ions, water molecules, and proteins as well as their ability to form stable networks in foams can influence and control macroscopic properties such as taste and texture of dairy products considerably. Despite the significant relevance of protein adsorption at liquid interfaces, a molecular level understanding on the arrangement of proteins at interfaces and their interactions has been elusive. Therefore, we have addressed the adsorption of the model protein bovine serum albumin (BSA) at the air-water interface with vibrational sum-frequency generation (SFG) and ellipsometry. SFG provides specific information on the composition and average orientation of molecules at interfaces, while complementary information on the thickness of the adsorbed layer can be obtained with ellipsometry. Adsorption of charged BSA proteins at the water surface leads to an electrified interface, pH dependent charging, and electric field-induced polar ordering of interfacial H 2O and BSA. Varying the bulk pH of protein solutions changes the intensities of the protein related vibrational bands substantially, while dramatic changes in vibrational bands of interfacial H 2O are simultaneously observed. These observations have allowed us to determine the isoelectric point of BSA directly at the electrolyte-air interface for the first time. BSA covered air-water interfaces with a pH near the isoelectric point form an amorphous network of possibly agglomerated BSA proteins. Finally, we provide a direct correlation of the molecular structure of BSA interfaces with foam stability and new information on the link between microscopic properties of BSA at water surfaces and macroscopic properties such as the stability of protein foams. © 2012 American Chemical Society.
Created from Fastlane, Scopus look-up